Long-Term Dentin Bonding Performance of Universal Adhesives: The Effect of HEMA Content and Bioactive Resin Composite - Di Wu; Ye Yao; Carolina Cecilia Cifuentes-Jimenez; Hidehiko Sano; Pedro Álvarez-Lloret; Monica Yamauti; Atsushi Tomokiyo (Journal of Functional Biomaterials)
This study investigated the effects of resin composites (RCs) containing surface pre-reacted glass ionomer (S-PRG) filler on the dentin microtensile bond strength (μTBS) of HEMA-free and HEMA-containing universal adhesives (UAs). Water sorption (WS) and solubility (SL), degree of conversion (DC), and ion release were measured. The UAs BeautiBond Xtreme (BBX; 0% HEMA), Modified Adhesive-1 (E-BBX1; 5% HEMA), Modified Adhesive-2 (E-BBX2; 10% HEMA), and two 2-step self-etch adhesives (2-SEAs): FL-BOND II (FBII; with S-PRG filler) and silica-containing adhesive (E-FBII) were used. Teeth were restored with Beautifil Flow Plus F00 with S-PRG filler (BFP) and flowable resin composite with silica filler (E-BFP). μTBS was evaluated after 24 h and 6 months of water storage. WS and SL measurement followed ISO 4049:2019; spectroscopy measured DC; ICP-MS evaluated ion release. BBX and FBII presented the highest DC. The adhesives did not comply with the WS ISO requirements, but the bonding resin of 2-SEAs complied with the SL threshold. BFP released more ions than E-BFP. BFP positively affected the μTBS of UAs, regardless of HEMA concentration after 24 h, comparable to the 2-SEAs. The 6 months μTBS decrease depended on the adhesive and RC combination. HEMA did not affect the μTBS of UAs, while bioactive resins had a positive impact.